(untitled) (Annals of Medical Research, 2022)
Aim: The aim of our study is to measure the levels of knowledge about the systemic toxicity of local anesthetics among anesthesia technicians, who will be the first to recognize local anesthetic systemic toxicity in the absence of an anesthesiologist or related physician. Materials and Methods: A total of 196 anesthesia technicians working at different hospitals were included in the study. A questionnaire was used as a data collection tool. The data obtained were evaluated statistically using IBM SSPS Statistics 25.0 for Windows. Results: When the distribution of the participants according to knowledge of systemic toxicity was examined, it was seen that 56.1% of the participants answered “yes” to having such knowledge, 24% of the participants said “no,” and 19.9% of the participants ​​did not remember. Regarding what must be done urgently in the event of local anesthetic systemic toxicity development, 74% of the participants said that the administration of local anesthetic should be stopped, 84.2% said that airway safety should be ensured, 100% said that oxygen should be administered, 65.3% said that a call for help should be made, 65.8% said that preparations for tracheal intubation should be started, 66.3% said that a safe venous line should be opened, 30.1% said that convulsions should be treated, and 51% said that a 20% lipid solution should be administered. Conclusion: Based on our findings, we conclude that anesthesia technicians need training to increase their awareness of and knowledge about the symptomatology, prevention, and treatment of local anesthetic systemic toxicity.